Proceedings of the 22nd ACM International Conference on Conference on Information &Amp; Knowledge Management - CIKM '13 2013
DOI: 10.1145/2505515.2505569
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive co-training SVM for sentiment classification on tweets

Abstract: Sentiment classification is an important problem in tweets mining. There lack labeled data and rating mechanism for generating them in Twitter service. And topics in Twitter are more diverse while sentiment classifiers always dedicate themselves to a specific domain or topic. Thus it is a challenge to make sentiment classification adaptive to diverse topics without sufficient labeled data. Therefore we formally propose an adaptive multiclass SVM model which transfers an initial common sentiment classifier to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 20 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…However this technique performed well for the domain of electronic products. [27] Proposed adaptive multiclass SVM model which works with topic adaptive sentiment classifier. The authors focused on non-text features to handle the sparsity of tweets.…”
Section: Related Workmentioning
confidence: 99%
“…However this technique performed well for the domain of electronic products. [27] Proposed adaptive multiclass SVM model which works with topic adaptive sentiment classifier. The authors focused on non-text features to handle the sparsity of tweets.…”
Section: Related Workmentioning
confidence: 99%
“…Support vector machine analyzes the data, define the decision boundaries and uses the kernels for computation which are performed in input space [15]. The input data are two sets of vectors of size m each.…”
Section: Support Vector Machinementioning
confidence: 99%
“…The experiment results indicated that ANN outperformed SVM on movie review data, but the training time of ANN is too long. Liu et al [16] proposed an adaptive multiclass SVM model for sentiment classification of tweets. The initial common sentiment classifier is transferred to a topic-adaptive one by optimization, unlabeled data selection and adaptive feature expansion.…”
Section: Sentiment Classificationmentioning
confidence: 99%